Current Overview on the Role of Nanoparticles in Water Desalination Technology - Shivalingam, Chitra; Mohan, Laksita; Ganapathy, Dhanraj; Shanmugam, Rajeshkumar; Pitchiah, Sivaperumal; Ramadoss, Ramya; Sundramoorthy, Ashok K. (Current Analytical Chemistry, 2022)
Background: Nanoparticles based thin-film has remarkable challenges in water desalination. Carbon allotropes (carbon nanotubes, graphene sheets, and fullerene), metal and metal oxide nanoparticulates (titanium dioxide, silver, copper oxide, alumina, zinc oxide, and metal-organic framework, silica, halloysite, zeolite, aquaporin and cellulose) are the out breaking materials for water desalination. Advanced materials in membrane forms are impacting the desalination processes in terms of reverse osmosis, forward osmosis, pervaporation, membrane distillation, and electrodialysis. Objective: The main objective of this review is to provide a comprehensive overview of the various methods of water desalination and the role of nanoparticles in this regard. Methods: We discussed the overall studies describing the process of desalination, viz. distillation, osmosis, freeze-thaw desalination, electrodialysis, membranes, various types of nanoparticles used in desalination, current techniques in desalination, membrane technology with Algae treatment, environmental issues in desalination, future scopes and trials. Conclusion: Various polymeric membranes with graphene/carbon derivatives and nano-particulate integrated membranes are gaining enormous attention in the field of membrane technology for the desalination process. Nanoparticulate impregnated, and natural algae conjugated polymeric membranes may provide a plethora of possibilities for membrane filtration technology in the near future.
Keywords: nanoparticles